Creeping attachment post-gingival recession treatment using a vestibular incision subperiosteal tunneling access technique combined with a connective tissue graft - Hapsari Kartika Prathivi; Rezmelia Sari (Dental Journal, 2023)
Background: The exposed roots of teeth due to gingival recession can generate dentin hypersensitivity and esthetic problems because a patient feels that the teeth, especially the anterior teeth, look long. Recession in thin anterior gingiva often brings unsatisfactory treatment results, so mucogingival surgery, such as vestibular incision subperiosteal tunneling access (VISTA) with the addition of a connective tissue graft (CTG), can be chosen as an appropriate treatment technique. Purpose: This case report describes the creeping attachment phenomenon after treatment of anterior gingival recession with VISTA and CTG techniques. Case: A 28-year-old female patient came with Miller Class I gingival recession in thin anterior gingiva and malposition teeth, complaining about pain and esthetic problems. Case management: The patient was treated with a VISTA technique combined with CTG. The creeping attachment phenomenon seen at three months postoperatively obtained good root coverage so that the patient’s complaints were resolved even though periodic control was needed to evaluate oral hygiene. Conclusion: VISTA and CTG techniques are appropriate for treating anterior mandibular gingival recession with minimal trauma and provide significant results.